Safety Evaluation of SH003 and Docetaxel Combination in Patients With Breast and Lung Cancer: A Multi-Center, Open-Label, Dose Escalation Phase I Clinical Trial - Chunhoo Cheon KMD, PhD; Hwimun Kim KMD, MPH; Seok Yun Kang MD; Sung Yong Lee MD, PhD; Kyong Hwa Park MD, PhD; Seong-Gyu Ko KMD, PhD (Integrative Cancer Therapies)
Background: Cancer remains one of the leading causes of death worldwide, underscoring the need for novel therapies. SH003, an herbal mixture composed of Astragalus membranaceus , Angelica gigas , and Trichosanthes kirilowii , is a traditional Korean medicine formulation with potential to enhance chemotherapy efficacy and reduce toxicity. This study aimed to assess the safety and determine maximum tolerated dose of SH003 in combination with docetaxel in patients with advanced solid tumors, specifically lung and breast cancer. Methods: This Phase I, multi-center, open-label, dose-escalation study enrolled patients with advanced lung or breast cancer. Participants received SH003 orally at doses of 2400, 3600, or 4800 mg daily, alongside intravenous docetaxel (75 mg/m²) every 21 days. A 3 + 3 dose-escalation design was employed to determine the maximum tolerated dose. Safety assessments and adverse event monitoring were conducted at each treatment cycle. Results: Twelve participants were enrolled. SH003 was well tolerated up to 4800 mg/day, with no dose-limiting toxicities attributed to SH003. The most common adverse events were neutropenia, primarily associated with docetaxel, and mild dermatologic reactions such as eczema, rash acneiform, and pruritus. Preliminary evidence of disease stabilization was observed in several participants. Conclusion: The combination of SH003 and docetaxel demonstrated a favorable safety profile, with 4800 mg/day identified as maximum tolerated dose for SH003. These findings support further investigation in Phase II trials to assess therapeutic efficacy. Trial Registration: Clinical Research Information Service ( https://cris.nih.go.kr ) KCT0004770.